2021
DOI: 10.1101/2021.02.16.431383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Auditory Remapping Across the Sleep-Wake Cycle

Abstract: In a single day we transition from vigilant wakefulness to unconscious sleep and dreaming, undergoing diverse behavioural, physiological and neural changes. While during the awake state, exogenous stimuli and endogenous changes lead to sensory reorganisation, this remapping has not been charted throughout the sleep-wake cycle. We recorded neural activity in response to a range of tones using electroencephalography during a full-night sleep, and examined whether auditory responses become more similar, dissimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 156 publications
(220 reference statements)
0
3
0
Order By: Relevance
“…Moreover, in this study, we did not find significant differences in highorder responses to meter frequencies between stages 2 and 3 of NREM sleep, as opposed to previous studies showing that electrophysiological responses associated with high-order processes such as correct semantic categorization of a previously automatized task (Kouider et al 2014;Andrillon et al 2016) or selective amplification of meaningful over noninformative competing speech streams (Legendre et al 2019) can be found during light stage 2, NREM, whereas these responses vanish in deeper stage 3 of NREM sleep. These discrepancies may be explained by contextual and task-related differences across stimuli and experiments (Andrillon and Kouider 2020) and speak of the dynamic nature of auditory processing across vigilance stages (Arzi et al 2021;Wielek et al 2021).…”
Section: Selective Attenuation Of Meter Frequencies Across Sleep Stag...mentioning
confidence: 99%
“…Moreover, in this study, we did not find significant differences in highorder responses to meter frequencies between stages 2 and 3 of NREM sleep, as opposed to previous studies showing that electrophysiological responses associated with high-order processes such as correct semantic categorization of a previously automatized task (Kouider et al 2014;Andrillon et al 2016) or selective amplification of meaningful over noninformative competing speech streams (Legendre et al 2019) can be found during light stage 2, NREM, whereas these responses vanish in deeper stage 3 of NREM sleep. These discrepancies may be explained by contextual and task-related differences across stimuli and experiments (Andrillon and Kouider 2020) and speak of the dynamic nature of auditory processing across vigilance stages (Arzi et al 2021;Wielek et al 2021).…”
Section: Selective Attenuation Of Meter Frequencies Across Sleep Stag...mentioning
confidence: 99%
“…The first consists of assessing sensory neural responses to external stimuli, typically by measuring the latency and presence or absence of AEP components (Fischer et al, 2004; Nourski et al, 2018; Perrin et al, 1999; Ruby et al, 2008; Sculthorpe et al, 2009; Tivadar et al, 2021). NREM sleep AEPs are characterised by higher amplitude components, occurring at greater latencies than wake AEPs (Arzi et al, 2021; Colrain & Campbell, 2007; Yang & Wu, 2007). To this, we add that neural responses to auditory stimulation have reduced neural complexity and a steeper spectral slope during sleep relative to wakefulness.…”
Section: Discussionmentioning
confidence: 99%
“…The activity observed following the neutral words will be correlated to that following the negative and positive words to determine whether the patients' information processing during sleep in negatively biased. Methods for monitoring cognitive processing during sleep based exclusively on sleep data have been successfully used in a number of recent studies (e.g., [9][10][11][12]).…”
mentioning
confidence: 99%